2023
DOI: 10.1186/s40035-023-00355-z
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity as a risk factor for cognitive impairment and Alzheimer’s disease

Abstract: Neurological conditions, including cognitive impairment and Alzheimer’s disease (AD), impose a huge burden on society, affecting millions of people globally. In addition to genetic factors, recent studies indicate that environmental and experiential factors may contribute to the pathogenesis of these diseases. Early life adversity (ELA) has a profound impact on brain function and health later in life. In rodent models, exposure to ELA results in specific cognitive deficits and aggravated AD pathology. Extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 205 publications
(239 reference statements)
1
3
0
Order By: Relevance
“…Brain development is particularly vulnerable to the adverse effects of early life dysbiosis. 50 , 51 In this study, our results demonstrated that early life dysbiosis induced by insufficient H 2 O 2 levels of LAO1-absent breast milk impaired spatial learning in adults‘ Morris water maze test and object location test. A previous study also indicated that early life dysbiosis caused by antibiotic treatment from P1 to P28 induced a disability in spatial learning and memory in this test.…”
Section: Discussionsupporting
confidence: 53%
“…Brain development is particularly vulnerable to the adverse effects of early life dysbiosis. 50 , 51 In this study, our results demonstrated that early life dysbiosis induced by insufficient H 2 O 2 levels of LAO1-absent breast milk impaired spatial learning in adults‘ Morris water maze test and object location test. A previous study also indicated that early life dysbiosis caused by antibiotic treatment from P1 to P28 induced a disability in spatial learning and memory in this test.…”
Section: Discussionsupporting
confidence: 53%
“…Besides the main mechanisms discussed above, other potential mechanisms may also contribute to myelin degradation in the context of AD. Neuroinflammation and oxidative stress are common pathological events during the progression of AD [ 106 , 107 ]. The activation of various inflammatory signaling pathways and the accumulation of reactive oxygen species (ROS) are characteristic features of AD progression.…”
Section: Molecular Basis Underlying Myelin Degeneration During Ad Pro...mentioning
confidence: 99%
“…Studies have confirmed that psychosocial stress can lead to the imbalance of homeostasis and cause mental disorders such as depression, anxiety, addictive behavior, psychosis (Zhao et al, 2021;Phillips et al, 2015;Restrepo & Lemos, 2021;Abdel Wahed & Hassan, 2017;Magalhães et al, 2022;Colizzi et al, 2023;Mansueto & Faravelli, 2022), induce the crime (Liu, 2016), cause eating disorder or increase the suicide tendency (Degortes et al, 2014;Black et al, 2019;Polanco-Roman et al, 2016;Currier et al, 2016;Stack & Bowman, 2023). Researchs also indicated that psychosocial stress can lead to diabetes, asthma, vitiligo, alzheimer's disease, cardiovascular disease and aggravated the illness (Turin & Drobnič Radobuljac, 2021;Priftis & Anthracopoulos, 2008;Krüger et al, 2011;Amaducci et al, 1986;Huang et al, 2023;Khayyam-Nekouei et al, 2013;sun et al, 2017;Lutskyi et al, 2020;Matthews & Li, 2023). Chronic psychosocial stress can also induce malignant tumors, such as ovarian cancer and breast cancer (Lutgendorf et al, 2013;Bower et al, 2014).…”
Section: Introductionmentioning
confidence: 96%